Icariin Ameliorates Diabetic Cardiomyopathy Through Apelin/Sirt3 Signalling to Improve Mitochondrial Dysfunction - Ni, Tingjuan; Lin, Na; Huang, Xingxiao; Lu, Wenqiang; Sun, Zhenzhu; Zhang, Jie; Lin, Hui; Chi, Jufang; Guo, Hangyuan (Frontiers in Pharmacology, 2020)
Myocardial contractile dysfunction in diabetic cardiomyocytes is a significant promoter of heart failure. Herein, we investigated the effect of icariin, a flavonoid monomer isolated from Epimedium, on diabetic cardiomyopathy (DCM) and explored the mechanisms underlying its unique pharmacological cardioprotective functions. High glucose (HG) conditions were simulated in vitro using cardiomyocytes isolated from neonatal C57 mice, while DCM was stimulated in vivo in db/db mice. Mice or cardiomyocytes were treated with icariin, with or without overexpression or silencing expression of Apelin and Sirt3 via transfection with adenoviral vectors (Ad-RNA) and specific small hairpin RNAs (Ad-sh-RNA), respectively. Icariin markedly improved mitochondrial function both in vivo and in vitro, as evidenced by increased level of mitochondrial-related proteins via western blot analysis (PGC-1α, Mfn2, and Cyt-b) and increased mitochondrial membrane potential, as observed via JC-1 staining. Further, icariin treatment decreased cardiac fibrogenesis (Masson staining), and inhibited apoptosis (TUNEL staining). Together, these changes improved cardiac function, according to multiple transthoracic echocardiography parameters, including LVEF, LVSF, LVESD, and LVEDD. Moreover, icariin significantly activated Apelin and Sirt3, which were inhibited by HG and DCM. Importantly, when Ad-sh-Apelin and Ad-sh-Sirt3 were transfected in cardiomyocytes or injected into the heart of db/db mice, the cardioprotective effects of icariin were abolished and mitochondrial homeostasis were disrupted. Further, it was postulated that since Ad-Apelin induced different results following increased Sirt3 expression, icariin may have attenuated DCM development by preventing mitochondrial dysfunction through the Apelin/Sirt3 pathway. Hence, protection against mitochondrial dysfunction using icariin may prove to be a promising therapeutic strategy against DCM in diabetes.